Assessment of agricultural policies to implement soil organic carbon (SOC) commitments in NDCs: Examples from Brazil and Rwanda - Wiese-Rozanova, Liesl D.; Rose, Sabrina; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Countries with national agricultural policies providing quantified SOC-related mitigation actions and commitments can increase NDC transparency by referring to such policies and associated actions in their NDCs.